The Study of Schedule-Oriented Planning for Efficient Construction Project Management - Yong, Yin Yin; Zainal, Rozlin; Kasim, Narimah (Research in Management of Technology and Business, 2026)
The global and Malaysian construction industries are experiencing a transformation driven by rapid urbanisation, sustainability demands, and digitalisation, while also facing challenges such as rising material costs, labour shortages, and growing project complexity. This study aims to identify key challenges in schedule-oriented planning, determine effective strategies, and analyse their relationship using a quantitative approach. The respondents were project managers from G7 contractor companies in Klang, Selangor. There were a total of 33 valid responses were analysed using descriptive and Spearman’s correlation analyses in SPSS. The findings found that environmental disruptions, inadequate project management tools, and resource constraints are the most significant challenges affecting project schedules. The findings found that environmental disruptions, inadequate project management tools, and resource constraints are the most significant challenges affecting project schedules. In contrast, leadership development, advanced planning and scheduling systems, and labour management strategies are identified as the most effective strategies. The analysis further indicates that the relationships between challenges and strategies are generally weak to moderate, with the strongest relationships being those between mismatched tools and training in communication skills. The results confirm a significant relationship between scheduling challenges and the strategies used to address them, highlighting the importance of proactive planning and effective management in improving construction project performance.